Attitude control of rigid spacecraft with predefined-time stability. Issue 7 (May 2020) - Wang, Feng; Miao, Yue; Li, Chaoyong; Hwang, Inseok
Abstract: This paper investigates the attitude tracking problem of a rigid spacecraft using contemporary predefined-time stability theory. To this end, the relative attitude kinematic and dynamic models of a spacecraft are presented. Then, a sliding mode surface and predefined-time stability theory are applied to ensure that both the tracking errors of the attitude, expressed by the quaternion and the angular velocity, converge to zero within a prescribed time. Simulation results demonstrate the performance of the proposed scheme.